USM STUDENTS HELP PRIMARY SCHOOL CHILDREN IN KUALA KANGSAR IMPROVE THEIR ENGLISH - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGE TOWN, PENANG, 7 March 2016 Universiti Sains Malaysia (USM) Secretariat of Asia Pacific Alliance of Postgraduate Student Association (USM APAPSA) recently organised a community teaching programme named the English Talent Development Programme to teach English to school children in several primary schools in the Kuala Kangsar district in Perak.